Pengaruh Tingkat Pendidikan, Struktur Ekonomi dan Belanja Pembangunan Terhadap Kemiskinan Provinsi Bali - Eka Suputra, I Putu; Martini Dewi, Ni Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 2, Februari 2015 (pp.71- 137), 2015)
Poverty is no longer understood only as the lack of economic, but also the failure to meet basic rights and”discrimination”against”a”person or”group”of”people”in the experience of life with dignity. Province of Bali  has gradually been working to reduce poverty through the implementation of the strategy undertaken by the pro-people programs and provide adequate means ”to” be ”able” to ”access” a ”variety” of ”services” and ”meet the needs” of ”the” community.”This study”was”conducted”to”determine”the influence of education”level,”Economic Structure and Development Expenditure on Poverty in the district / city in the Province of Bali. Source of data used is secondary data using panel data (time series data for 6 years and the cross section as much as 9 district / city).”The”data”analysis”technique”used”is”multiple”linear”regression”analysis SPSS.”Result of application has obtained show that simultaneous Level of Education, Economic Structure and Development Expenditure significant effect on poverty in the district / city in the province of Bali. Partially, Level of Education and Development Expenditure negative effect, while the Economic Structure positive effect on poverty in the district / city in the Province of Bali.
Keywords: poverty, education level, economic structure and development expenses